Fenomena Ketidaksopanan Berbahasa Indonesia Pada Saat Bermain Game Online - Akbar, Muh. Fadhil; Akram, M.; Fiddienika, Arief (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2024)
This research highlights the role of sociolinguistics in the context of linguistic impoliteness during online gaming. Using a literature review method, the study finds that linguistic impoliteness reflects moral degradation and can disrupt player relationships. Sociolinguistics is essential for understanding language behavior dynamics, considering social, cultural, and contextual influences. The study emphasizes the need for active roles from individuals and communities in creating positive communication and the importance of character education to minimize impoliteness.